Exploration of photonic networks on chip with the University of Ferrara - Ortín, Marta (Jornada de Jóvenes Investigadores del I3A, 2014)
Modern chips include several processors that communicate through an interconnection network, which has a direct impact on system performance, power consumption and chip area. Recent research points out the great potential of optical networks to reduce on-chip communication latency and energy. We plan to explore this state-of-the-art field during an internship in the University of Ferrara.